Electrochemical Cutting of Micro-Holes in Tubular Stepped Concentrator-Waveguide for Medical Purposes - Yu. G. Aliakseyeu; A. Yu. Korolyov; A. S. Budnitskiy; Dai Wenqi (Наука и техника)
A great attention has been recently paid to development of ultrasound technologies for treatment of blood vessels throughout the world. Authors of the paper have developed a new effective treatment method and ultrasound equipment that allow to carry out destruction of intravascular formations with simultaneous increase in elasticity of a vascular wall together with cardiologists from Belarusian Medical Academy of Postgraduate Education and Republican Scientific and Practical Center “Cardiology”. Advantages of the method are absence of necessity in surgical intervention, low probability of complications, low cost of treatment. The main component of the developed ultrasonic equipment is a tube-type stepped concentrator-waveguide having a spherical tip at a distal end with a single axial hole of 0.5 mm-diameter and three radial holes of 0.3 mmdiameter located at an angle of 120° relative to each other. The main effect for application of the concentratorwaveguide is achieved by ultrasonic vibromechanical action of a spherical tip on intravascular formation with subsequent removal of destruction products by their aspiration from a vascular bed. An additional effect is provided due to cavitation action on vascular formation and vessel walls by flow of fluid supplied via an internal cavity of the stepped concentratorwaveguide through the holes in the spherical tip. This contributes to a significant improvement in elastic properties of a vascular wall in atherosclerosis and diabetes. It is necessary to ensure high accuracy and quality of surfaces for the formed microholes in order to achieve maximum efficiency of the cavitation jet impact on intravascular formations and on the vascular wall. According to the analysis results on specific features of existing methods for small-diameter hole shaping, an electrochemical hole cutting method has been proposed which allows to obtain accurate micro-holes with a diameter of 0.3 mm and high surface quality in parts of small cross section and rigidity. The paper presents results of study on effect of electrochemical holes cutting parameters (voltage, concentration and consumption of electrolyte) on size and shape of the formed microholes. Main modes of electrochemical holes cutting process have been developed which allow to form micro-holes in a spherical tip of a tubular concentrator-waveguide with required accuracy, dimensions and shape.